2005
DOI: 10.1055/s-2005-870320
|View full text |Cite
|
Sign up to set email alerts
|

Pioneer Study: PPARγ Activation Results in Overall Improvement of Clinical and Metabolic Markers Associated with Insulin Resistance Independent of Long-term Glucose Control

Abstract: New scores and biochemical markers have recently been published for diagnosis of insulin resistance and beta-cell dysfunction (such as intact proinsulin, adiponectin, IRISII-score). One goal of this 6-month prospective controlled study was to evaluate the impact of pioglitazone (45 mg) vs. glimepiride (1-6 mg, in the intend to optimize therapy) on these markers. Observation parameters were: IRIS-II score, HOMA-score, ATP III score, HbA (1c), fasting glucose, lipids, intact proinsulin, adiponectin, and adverse … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
31
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 26 publications
2
31
0
Order By: Relevance
“…In contrast to insulinsensitizing strategies, sulfonylureas have been reported not to change or to increase plasma proinsulin values. 26,28,31,36,38,41,[48][49][50] Preliminary studies revealed that the fasting proinsulin serum concentration was significantly higher in T2DM patients treated with sulfonylureas than in a well-matched group receiving insulin only. 49 One of our studies explored the immediate effect of supplementary insulin treatment on beta-cell function in 20 T2DM patients with glimepiride monotherapy.…”
Section: Results With Other Insulin-sensitizing Strategies and Insulimentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast to insulinsensitizing strategies, sulfonylureas have been reported not to change or to increase plasma proinsulin values. 26,28,31,36,38,41,[48][49][50] Preliminary studies revealed that the fasting proinsulin serum concentration was significantly higher in T2DM patients treated with sulfonylureas than in a well-matched group receiving insulin only. 49 One of our studies explored the immediate effect of supplementary insulin treatment on beta-cell function in 20 T2DM patients with glimepiride monotherapy.…”
Section: Results With Other Insulin-sensitizing Strategies and Insulimentioning
confidence: 99%
“…No such effects were observed in the glimepiride group. 28 Another analysis of the PIONEER data substantiated that measurement of intact proinsulin enables an estimation of atherosclerotic risk.…”
Section: Pioglitazone In Comparison To Sulfonylurea Administrationmentioning
confidence: 99%
“…However, prospective studies using the same diagnostic markers as used in our current analysis have provided evidence of a beneficial impact of other therapeutic interventions compared to sulfonylurea therapy. Treatment of insulin resistance, e.g., using PPARg agonists seems to be an effective measure for decreasing cardiovascular and metabolic risk (29)(30)(31)(32).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to decreasing insulin resistance and ␤-cell dysfunction (47), increasing serum HDL cholesterol and decreasing serum triglycerides levels (25), improving the procoagulant state and endothelial dysfunction in diabetes, and reducing "nontraditional" inflammatory cytokines (12), thiazolidinediones have been shown to reduce myocardial infarct size (IS) in the rat (35,61,66,67). However, the specific underlying mechanisms for myocardial protection by thiazolidinediones are still unknown.…”
mentioning
confidence: 99%